Requirements for intermediaries and advisors in the area of mortgages resulting from Mortgage Credit Directive: Implications for Poland - Krzysztof Waliszewski (e-Finanse: Financial Internet Quarterly, 2015)
The dynamic development of the mortgage market, especially in the period before the current financial crisis, revealed that within the EU there are local mortgage credit markets and that it is necessary to harmonize the rules of the system and consumer protection within the Community. The intention of the creators of the Mortgage Credit Directive was to organize the mortgage lending market for residential purposes and make it transparent, as well as increase the safety of the consumer credit market, along the lines of what took place earlier in the consumer credit market regulations (The Consumer Credit Directives no. 2008/48/EC and earlier no. 87/102/EEC). The Mortgage Credit Directive implies for lenders - credit institutions to act at every stage of the lending process with respect to the consumer's interest and to provide them with adequate services for their needs. Due to the large role of indirect distribution channels of mortgages by banks there are certain requirements for intermediaries, brokers and credit advisors. The implementation term of the Directive, appointed for March 2016, implies action to be taken in order to implement the provisions of this Directive into Polish law. The legislative process is being conducted by the Ministry of Finance and supported by the Group on implementation of the Mortgage Credit Directive operating with the Council of Financial Market Development.
Keywords: D14; D18; E51; G21; 330; credit intermediaries; credit advisors; mortgage credit market; Mortgage Credit Directive (MCD)